2009
DOI: 10.1134/s1063776109120073
|View full text |Cite
|
Sign up to set email alerts
|

Strong suppression of Coulomb corrections to the e + e − pair production cross section in ultrarelativistic nuclear collisions

Abstract: The Coulomb corrections to the cross section of e + e − pair production in ultrarelativistic nuclear collisions are calculated in the next-to-leading approximation with respect to the parameter L = ln γAγB (γA,B are the Lorentz factors of colliding nuclei). We found considerable reduction of the Coulomb corrections even for large γAγB due to the suppression of the production of e + e − pair with the total energy of the order of a few electron masses in the rest frame of one of the nuclei. Our result explains w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…To solve the inconsistency, Lee and Milstein [23] constructed an appropriate regularization by introducing a screening of the Coulomb potential, which resulted in a large negative correction to the total cross section. However, with the multiple pair production taken into account [24], the higher-order effect for total cross section became small. Following this strategy, the hint of higher-order effect [25,26] had been observed in comparison with the RHIC measurements.…”
Section: Jhep08(2021)083mentioning
confidence: 99%
“…To solve the inconsistency, Lee and Milstein [23] constructed an appropriate regularization by introducing a screening of the Coulomb potential, which resulted in a large negative correction to the total cross section. However, with the multiple pair production taken into account [24], the higher-order effect for total cross section became small. Following this strategy, the hint of higher-order effect [25,26] had been observed in comparison with the RHIC measurements.…”
Section: Jhep08(2021)083mentioning
confidence: 99%
“…It is, however, important to realize that most of those Coulomb corrections are only effective for photon energy of a few MeV in the rest frame of the target nucleus. Therefore, none of the conditions presented in equation ( 4) of [128] for such a correction are satisfied in the situation under discussion in this review. It has been argued and demonstrated that Coulomb corrections in the kinematics relevant to the BW process under discussion (γ 1,2 ≫ 1 and γ/R ≫ ω 1,2 ≫ 1/R) are vanishingly small (<1%) [80,125,[129][130][131].…”
Section: Higher Order Processes In Qedmentioning
confidence: 92%
“…Coulomb effects cancel exactly) [131]. On the other hand, it may be possible that such Coulomb corrections are indeed present at the LHC through the dimuon channel [116,132] with photon energy of m µ ≪ ω ≃ 10 GeV ≪ γm µ ≃ 250 GeV, in the expected range for significant Coulomb corrections [128] but may be absent in the e + e − channel [133]. In this context of a negligible non-perturbative QED effect, some experts [80] concluded in dismay 15 years ago: 'In April 1990 a workshop took place in Brookhaven with the title "Can RHIC be used to test QED?"…”
Section: Higher Order Processes In Qedmentioning
confidence: 95%
“…The A A → A A + − reaction was also discussed in the literature [37][38][39][40][41][42][43][44][45][46]. In Fig.…”
Section: A Comment On Quantum Multiple-photon Exchange Effectsmentioning
confidence: 93%